DECONGESTANTS AND THEIR SIDE EFFECTS FOR TREATMENT OF ACUTE RHINITIS IN CHILDREN (CLINICAL EXAMPLE) - Елена Владимировна Пшеничная; Александра Петровна Дудчак; Надежда Алексеевна Усенко (The Publishing House Medicine and Enlightenment, 2018)
Nasal decongestants are effective and most commonly used medications for the symptomatic treatment of acute rhinitis in children. Despite new approaches to therapy, modern clinical practice guideline for the treatment of acute rhinitis in children, a wide selection of topical vasoconstrictive medications and their availability create conditions for uncontrolled use of these medications and determine the relevance of the problem of side effects. The article gives a brief overview of the use of decongestants in acute rhinitis in pediatric practice, their side effects are examined, a clinical case of Naphthyzin poisoning of a three-year-old child is described. A peculiarity of this case is the development of a life-threatening state in a patient. The authors draw attention to the importance of the correct prescribing of the described medications, a thorough explanation of the parents' side effects of vasoconstrictive medications, including the emergence of life-threatening conditions for the child.